The Ovid Java Client Interface: a comparison with the Ovid Web Gateway and Windows client interfaces. - Cavanaugh BB (Medical Reference Services Quarterly, 1998)
The Ovid Java interface is compared with the Ovid Web Gateway and Ovid Windows Client. The focus is on functionality from the user's perspective. The Java version draws upon both the earlier Web and Windows versions, thus combining the worlds of the Web and application programs. It is concluded that Ovid Java offers enhanced functionality and requires high-end hardware and browser software to run well. Additional enhancements are forthcoming, some dependent upon the further development of Sun Microsystems' Java programming language.